Efeitos da idade no desempenho de uma amostra brasileira saudável no Teste Faux Pas de Teoria da Mente (ToM) - Saad, Flavia Mazzariolli [UNIFESP] (2018)
Abstract: Introduction: Theory of Mind (ToM) is the capacity to infer a thought, mental states for himself and for others. There are two different components to be observed in ToM: the affective (ToM-a), in which the individual infers emotional states or perceives feelings; and the more complex cognitive ToM (ToM-c), which depends on the understanding of the other's perspective. Objectives: In this study we observed the correlations between the different components of ToM and the aging process through a sample of cognitively healthy individuals. Method: Cognition was evaluated by the Addenbrooke's Cognitive Examination - Revised ACE-R (which evaluates five cognitive domains: Attention and Guidance, Memory, Fluency, Language and Visual- Spatial Skills) was presented to the selected individuals who then responded to the Faux Pas Test (FPT), in which 20 stories are presented: 10 containing a gaffe and 10 in which nothing wrong or strange happens. The individual must recognize both conditions. Results: In this group there was no significant correlation between the performance in the FPT and age. A division was made between people under 60 and over 61 years to analyze the effect of aging performance. There was no significant difference in the detection of gaffes comparing both groups. The ACE scale demonstrated that this performed better in the sub-tests of Language, Memory, and Attention, visuo-spatial and fluency, in that order; more specifically, the test demonstrated that there is a significant correlation between performance in ACE and the correct identification of stories with Faux Pas. The cognitive domains that most contributed to this significant interaction were attention-orientation and memory. There was a trend to worse performance with increasing age for ToM-c, followed by intention (ToM-a), then empathy (ToM-a) and lastly, inadequacy (ToM-c).